The Multiple Representations Integrated Interactive Flipbook to Improve Students' Chemistry Learning Outcomes: Multiple Representations Integrated Interactive Flipbook - Erna Risdiana, Erna Risdiana (Balai Diklat Keagamaan Denpasar, 2025)
The characteristics of chemistry are full of abstract and complex concepts. The process of learning chemistry, especially Redox material, tends to only explain chemical concepts at the macroscopic and symbolic levels and does not relate to the submicroscopic level. This results in the concept of Redox material as a whole being difficult for students to understand and results in low interest and learning outcomes. The purpose of this study was to improve the chemistry learning outcomes of MAN Buleleng students using the implementation of an integrated multiple representation learning design of interactive flipbooks on Redox material. This study was conducted through two cycle stages with two meetings in each cycle using multiple representation syntax assisted by interactive flipbook learning media that can be accessed online. The success of the implementation of integrated multiple representation learning of interactive flipbooks can be seen from the continuous increase in learning outcomes of 16.13% in Cycle I and 9.8% in Cycle II. The application of integrated multiple representation learning of interactive flipbooks shows an increase in student learning outcomes in redox material. The results of this study can be used for the process of improving chemistry learning at MAN Buleleng in particular and the learning process in other schools in general.